PACAP/GCGa Is an Important Modulator of the Amphioxus CNS-Hatschek’s Pit Axis, the Homolog of the Vertebrate Hypothalamic-Pituitary Axis in the Basal Chordates - On, Jason S. W.; Su, Liuru; Shen, Hong; Arokiaraj, Aloysius W. R.; Cardoso, João C. R.; Li, Guang; Chow, Billy K. C. (Frontiers in Endocrinology, 2022)
The Hatschek’s pit in the cephalochordate amphioxus, an invertebrate deuterostome basal to chordates is suggested to be the functional homolog structure of the vertebrate adenohypophysis based on anatomy and expression of homologous neuroendocrine genes. However, the endocrine potential of the cephalochordate Hatschek’s pit remains to be demonstrated as well as the physiological actions of the secreted neuropeptides. In this study, we have explored the distribution and characterize the potential function of the amphioxus PACAP/GCG precursor, which is the ortholog of the hypothalamic PACAP neuropeptide in vertebrates. In amphioxi, two PACAP/GCG transcripts PACAP/GCGa and PACAP/GCGbc that are alternative isoforms of a single gene with different peptide coding potentials were isolated. Immunofluorescence staining detected their expression around the nucleus of Rohde, supporting that this structure may be homologous of the neurosecretory cells of the vertebrate hypothalamus where abundant PACAP is found. PACAP/GCGa was also detected in the infundibulum‐like downgrowth approaching the Hatschek’s pit, indicating diffusion of PACAP/GCGa from the CNS to the pit via the infundibulum‐like downgrowth. Under a high salinity challenge, PACAP/GCGa was upregulated in amphioxi head and PACAP/GCGa treatment increased expression of GHl in Hatschek’s pit in a dose-dependent manner, suggesting that PACAP/GCGa may be involved in the regulation of GHl via hypothalamic-pituitary (HP)-like axis similar as in the vertebrates. Our results support that the amphioxus Hatschek’s pit is likely to be the functional homolog of pituitary gland in vertebrates.